Natureza, sociedade e educação moral em Rousseau : do Segundo Discurso ao livro IV do Emílio - Stürmer, Adroaldo (2009)
The opposition between nature and society is a constant in the thought of Rousseau. Rolls his works, we can see that man‟s nature is good, while the social man is the subject corrupted. But nevertheless, the theory of Rousseau is that society is one place where the natural man can be moral, or social produces the specific conditions where they can sprout feelings of solidarity addressing the processes of corruption. The purpose of this study is to investigate through a reconstructive analysis of key passages the Segundo Discurso and the Book IV of Emílio, as is thought the relationship between nature and sociality, and that this relationship is a concept of human being is able to guide their action on the basis of their conscience in the moral. In this context we must understand how Rousseau defines nature as education and social needs get this concept the reference standard for their pedagogical action